A Case Report of Salvage Radiotherapy for a Patient with Recurrent Gastric Cancer and Multiple Comorbidities Using Real-time MRI-guided Adaptive Treatment System - Chun, Seok-Joo (Cureus, 2018)
The stomach is one of the most deforming organs caused by respiratory motions and daily variation by food intake. Applying radiotherapy has been quite a challenge due to the high risk of missing the target as well as radiation exposure to large volumes of normal tissue. However, real-time magnetic resonance (MR)-guided radiotherapy with adaptive planning could focus the high dose radiation to the target area while minimizing neighboring normal tissue exposure and compensate for not only daily but real-time variation. Here is a case report of a patient with recurrent gastric cancer and multiple co-morbidities, unsuitable for both resection and chemotherapy, who underwent MR guided adaptive radiotherapy.